The Role of the National Economic Recovery Program on MSMEs’ Sustainability in the Perspective of Maqashid Sharia - Muhammad Alfan Rumasukun (IQTISHADIA, 2023)
The purpose of this research is to identify the Implementation and Implications of Indonesian Government's National Economic Recovery (NER) Program on MSMEs in East Java Province with their harmony and relevance to Maqashid Sharia by Jasser Auda who has studied and aligned them with human activities and conditions in modern era. This study uses Policy Research with Qualitative Descriptive Approach. The data source is explored through an interview and documentation process from informants as MSMEs business people in East Java who have received assistance from the Government through the NER Program, which based on eachconfession that government assistance greatly helps the sustainability of their business in the midst of an economic crisis during the pandemic. As can be seen from the NER Program policy, positive results were obtainedfrom the implementation and implications of Government assistance through the program to MSMEs business actors in East Java Province. The program provides results that also meet the Maqashid Sharia standards stated by Jasser Auda. In addition, the policies carried out by the Government during the Pandemic were proven to be in accordance with the teachings of the Prophet Muhammad SAW and Umar bin Khattab when facing the Pandemic in their time.